The Influence of Nutritional Factors on the Quality of Life of Cancer Patients: A Scooping Review - Dhanang Efendi; Zulfikar Naftali; Fitria Handayani (Indonesian Journal of Global Health Research, 2024)
Cancer is a condition of abnormal cell growth, cells lose their normal control and mechanisms resulting in rapid and uncontrolled cell growth, as well as local tissue invasion and distant metastases. Quality of life is influenced by health status. A decrease in nutritional status often occurs as a result of cancer and its therapy. Due to the lack of food intake such as appetite, swallowing ability, absorption in the body and treatment therapy actions taken, coupled with chemotherapy. The aim of this study was to determine the effect of nutrition on the quality of life of cancer patients. Methods: Researchers used the scoping review method. The article search used databases from Sciencedirect, Scopus, and Pubmed with the research time January 2019 to December 2023, with the keywords influence"AND ‘nutrition’ AND ‘quality life’ AND ‘Patient’ AND ‘Cancer’. The results were 10 articles analyzed, all of which were quantitative articles. Based on identification, there are 67 articles from search engines from Sciencedirect, Scopus, and Pubmed. The final results obtained were 10 articles that fit the criteria after going through the selection process. Nutritional factors have an important role in the quality of life of patients. The better the nutrition obtained, the higher the patient's quality of life. Researchers used the PEO question format (population, exposure, outcome) to find related research articles. Improved nutrition helps prevent weight loss, which can affect tolerance to treatment and reduce its side effects. The nutritional status of cancer patients tends to change and deteriorate during intensive treatment. Maintenance of a healthy weight during cancer therapy is considered important in health management. By understanding the relationship between nutrition, diet and quality of life in cancer patients, appropriate nutrition interventions can be designed to improve treatment outcomes and patient well-being.